Efecto de la tasa de cambio real en la balanza por cuenta corriente en países con distintos niveles de desarrollo - Rafael Alvarado; Andrés Campoverde; Verónica Sánchez (Atlantic Review of Economics (ARoEc), 2018)
– The objective of this research is to examine empirically the relationship between the current account balance and the real exchange rate for economies with different levels of development. We use data from the annual time series of the period 1980-2015 from the Development Indicators (2017) of the World Bank for Ecuador, Chile and Germany. The selection of the sample of countries allows comparing the results between countries with significant differences in the level of economic development. Using cointegration and error correction techniques, we found robust empirical evidence suggesting that the Marshall-Lerner condition is not met for the sample of countries and there is a short-term equilibrium but not in the long term, with the exception of Ecuador, a country without monetary sovereignty. One implication of economic policy derived from this research is that the deficit can be cover ed by the increases in the capital and financial accounts using the reserve assets to balance the accounts. However, this situation is not sustainable indefinitely because the reserve assets would be exhausted and in the end, the real exchange rate would have to be depreciated.
Keywords: F32; F11; F14; C22; 330; Immigrant women; household work; labour conditions; labour and immigrant